New Strategies for Teaching English Language That Meet the Learners' Needs to the Secondary School Students (المجلة الدولية للعلوم التربوية والآداب, 2025)
With recent advancements in English instruction, it is essential to embrace all aspects of research in this field to fully understand the benefits that align with global developments. The researcher highlights several challenges encountered when exploring new trends that assist educators and students in improving English language learning and comprehension. The study is divided into three sections: the first provides an introduction, the second reviews the literature, and the third presents the study's conclusions along with the cited references.